Algebra 2 Common Core

Published by Prentice Hall
ISBN 10: 0133186024
ISBN 13: 978-0-13318-602-4

Chapter 6 - Radical Functions and Rational Exponents - Get Ready! - Page 357: 4



Work Step by Step

RECALL: (i) $(a^m)^n = a^{mn}$ (ii) $(ab)^m = a^mb^m$ (iii) $a^{-m} = \dfrac{1}{a^m}, a \ne0$ Use the rules above to have $3^2(x^{-4})^2(y^3)^2 \\=9x^{-4(2)}y^{3(2)} \\=9x^{-8}y^6 \\=\dfrac{9y^6}{x^8}.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.